التنافس التركي الإيراني في منطقة الخليج العربي 2014-1991 - بهي الدين وفاء (جامعة محمد بوضياف المسيلة, 2015)
منذ نهاية الحرب الباردة شهد العالم عدة تحولات جذرية، حيث انتقل من نظام ثنائية القطبية إلى نظام الأحادية. وفي ظل هذا التحول سعت بعض الدول الإقليمية كتركيا وإيران بسط وتكريس نفوذهما في منطقة الشرق الأوسط و بالأخصإقليم الخليج العربي. بالإضافةإلى هذه التغيرات الدولية، كنت للمتغيرات الداخلية التي مرت بها هاتين الدولتين في تسعينيات القرن الماضي أثرها الواضح في رسم سياستها الخارجية تجاه هذه المنطقة. ونظراً لأهمية هذه المنطقة الجيوستراتيجية التي اكتسبتها. إشتد التنافس بين البلدين بعد أحداث 11 سبتمبر 2001م وانهيار صدام حسين عام 2003م، لبسط نفوذهما في المنطقة وتوظيف كل معطياتهم التاريخية والجغرافية والثقافية لتأكيد الترابط بهذه الأخيرة وإظهار أنموذج دولتهما على انه الأنموذج المناسب والمثالي. ولياتي الحراك العربي والذي أوضح هذا التنافس بشكل جلي. كما كان للحراك العربي عام 2011م تأثيرا سواء ايجابيا آو سلبيا على الدولتين. وفي المقابل نجد إيران الرابح الأكبر من أحداث الحراك، حيث كانت الأزمة السورية كورقة رابحة لإيران للتفاوض مع الغرب فيما يخص برنامجها النووي. هذا ما ساهم في انفتاحها على دول الجوار وتكريس نفوذها في المنطقة.   Middle east region wintnessedseveral radical tronsformations since the end of the cold war while the worled shifted frombipolar to unipolar system ,. And under these conditions some regional nations like Turkey and Iran sought to exert their influence in that region. In addition to these international changes, internal changes undergone by these two nations in 1990s had clear effects on the way they draw their foreinpolicies towards Middle east region Owing to the importance of this region after september 11, 2001 and the fall of Saddam hussein regime in 2003, the two countries went in competition for influence over the region, and employed all their historical, geographical and cultural faces of power for asserting their connectedness and showing themselves as an example to be suitably followed, followed by the arab activism that demonstrated clearly the features of this competition. The first one was in support to the regime, while the second was baking the popular upheavalofsyrian people and harboring the opposition, which turned the relation between the two countries. In other side, Iran seems the big winner from the events of this activism so the crisis in seria was a winning card for negotiating the west regarding its nuclear program, which contributed in its opens towards neighbouring countries and asserting its influence in the region.
Keywords: العلاقات الدولية . ايران . تركيا .الخليج العربي . الإستراتيجيات الدولية . التنافس . الثورات العربية .التكتل الاقتصادي